STRATEGI PENGEMBANGAN DOESOEN KAKAO SEBAGAI DESTINASI WISATA EDUKASI DI BANYUWANGI - Ayu Purwaning Tyas; Eka Afrida Ermawati (Jurnal Pariwisata Pesona, 2020)
This research was done at Dosoen Kakao, Banyuwangi. The aims of this research are to find strength, weaknessess, opportunity and threath and also define the development strategy for Doeson Kakao as educational tourism destination in Banyuwangi. This research is a qualitatif research using SWOT analysis. This research results some strategis such as (1) SO strategy: expanding information, marketing and networking with travel agents, BPJS Ketenagakerjaan, and also networking with UMKM around Banyuwangi, marketing relationship is done in the form of co-marketing, and co-branding or public private partnership involvement, optimizing tools and equipments of education tourism, improving the inovation on chocolate products. ST strategy: improving  inovation and creativity in creating education tourism, urging tourists not to destroy plants in kakao plantation, community empowering in the destination by informing the value and the purpose of education tourism. WO strategy: Doing promotion and sosialisation especially in the form of word of mouthor electronic media about education tourism package, improving service quality and amenity quality by creating special feature, improving human resource competence through competence sertification or human resource tourism training by profession certification institution, adding supporting facilities, bureaucracy reformation. WT strategy: conducting promotion with various educational tourism packages to kill the boredom of the tourists.